2010
DOI: 10.1007/s11356-010-0306-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of particle number concentrations and PM2.5 in a school: influence of outdoor air pollution on indoor air

Abstract: The findings obtained in this study are useful for epidemiological studies to estimate the total personal exposure of children, and to develop appropriate control strategies for minimising the adverse health effects on school children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
3
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(89 citation statements)
references
References 54 publications
8
75
3
3
Order By: Relevance
“…Interestingly, the SOC proportion was higher outdoors than indoors for both size fractions, which might be due to the occurrence of photochemical reactions outdoors. Generally, walls and windows reduce sunlight in buildings, and consequently photochemical formation of SOC at indoors [55,56]. This is supported in this study by the fact that the average PM0.25 indoor SOC percentage was found to be the lowest.…”
Section: Estimation Of Soc From the Ec-tracer Methodssupporting
confidence: 79%
“…Interestingly, the SOC proportion was higher outdoors than indoors for both size fractions, which might be due to the occurrence of photochemical reactions outdoors. Generally, walls and windows reduce sunlight in buildings, and consequently photochemical formation of SOC at indoors [55,56]. This is supported in this study by the fact that the average PM0.25 indoor SOC percentage was found to be the lowest.…”
Section: Estimation Of Soc From the Ec-tracer Methodssupporting
confidence: 79%
“…In a study carried out in Shanghai, Huang et al (2009) found that low visibility, which is highly correlated with increased concentrations of PM2.5 and PM10, is significantly associated with elevated death rates from cardiovascular disease on the time scale of just one day. Guo et al (2010) found that outdoor air pollution has an hour-to-hour effect on indoor air pollution levels, meaning that staying inside (without air filtration) provides little respite from pollutants, to say nothing of those commuting by foot or bicycle. It is likely that it will be several decades before clean air is abundant enough in Chinese cities to be enjoyed by those who cannot afford prime real estate or air filtration systems.…”
Section: Resultsmentioning
confidence: 99%
“…In a European survey of 45 schools contents between 14 and 260 µg/m³ (PM 10 ) were measured (HESE, 2006). Different studies showed for PM 2.5 a ratio of indoor to outdoor air was in the range of 1 and a strong dependence on the outdoor air contents (Diapouli et al, 2007;Fromme et al, 2007;Wichmann et al, 2010;Guo et al, 2010). The situation is different if coarse particle fractions are considered.…”
Section: Particles In Residencesmentioning
confidence: 98%